THE CHALLENGE OF SCIENCE IN ISLAMIC EDUCATION IN ERA 4.0 - Hapidin, Ahmad; Natsir, Nanat Fatah; Haryanti, Erni (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
Critical analysis of the challenges of science in Islamic education in the 4.0 era, the goal is to realize superior knowledge in Islamic education, especially in the era of disruption (4.0), so that in this study etymologically it is necessary to uncover and explore the views of the reformers. Islam in responding to challenges in Islamic education in the 4.0 era. This research concludes that in realizing superior knowledge in Islamic education, especially in the era of disruption (4.0), the solution is, the knowledge needs to be adapted to the current developments, this is because science is 1) unraveling, 2) assist (supporters), in realizing the development of superior Islamic Education through the arguments contained in the Qur'an and Hadith. The real example is the establishment of formal schools, from elementary school (elementary school) to Islamic boarding school-based universities that exist in Indonesia. In addition, in order to develop superior science, it can be done through an alternative paradigm of integralism, which is integrated through religious sciences with non-religious sciences which can be done by Islamic boarding school-based institutions. As a result, the relevance of the views of Islamic reformers to the challenges of science in Islamic education in Era 4.0 is relevant, where this can be implemented through the development of superior Islamic education through the arguments contained in the Qur'an and Hadith. In addition, in forming a complete generation and competitive superior human beings, the concept of Islam demands to always think, be innovative, have character, be independent, and religious in facing Era 4.0, where humans are required to be fast, precise, effective and efficient in carrying out life activities.